Protein Profiling of Hirudo orientalis During Different Seasons for Obtaining Accurate Results in Leech Therapy - Amani, Leili; Ardakani, Mehran M.; Motamed, Nasrin; Malek, Masuomeh; Shasaltaneh, Marzieh Dehghan (Current Proteomics, 2023)
Objective: Leech therapy has been used for centuries as a recommended approach to cure several diseases, such as; psoriasis, arthrosclerosis, urinary tract diseases, and wound healing. The present study aimed to analyze the number, quantity, and distribution differences of medicinal leech (Hirudo orientalis) proteins throughout various seasons and in laboratory conditions as well.Methods: Protein profiling of salivary gland secretion from leech was studied by SDS-PAGE and 2D Electrophoresis on the proteins with the molecular weight range of 5 - 250 KDa in the lyophilized salivary gland secretion (SGS) during the seasons of summer and winter, and also in the laboratory conditions.Results: Our results indicated differences in the number and quality of leech saliva proteins in different seasons. We observed a higher number of proteins in summer than in winter. These results demonstrated the presence of Calin and Manillase in summer and Hyaluronidase and Collagenase in winter.Conclusion: This study could help us in choosing the best and most favorable conditions for using H. orientalis proteins for the treatment of different diseases.
Keywords: medicinal leech